Bio-waste to environmental purifier: Application of potato peel for acid red 73 adsorption from leather dyeing effluent - Fatema-Tuj Zohra; Sobur Ahmed; Md Zahangir Alam; Md Nurnabi; Nazia Rahman (Water Resources and Industry)
Potato peel powder (PP) was prepared from kitchen wastes and explored in removal of Acid Red 73 (AR 73) dye from leather dyeing effluent. PP was characterized through FTIR, BET, SEM, XRD and EDX analysis. SEM micrographs illustrated rough and porous structure of PP that support the adsorption process. FTIR spectrum exhibited the changes caused by formation of hydrogen bonding, complex bonding, or other electrostatic interaction after dye adsorption. Wide and frail peaks in the XRD image indicated existence of amorphous carbon. BET analysis exhibited mesoporous structure of PP with average pore diameter of 85.98 Å. The impact of various influences viz. pH, dosages, concentration, time and temperature were explored through batch investigation. The maximum AR73 dye adsorption capacity of PP was 258.39 mg/g. The dye adsorption on PP complied both the Langmuir (R2 = 0.989) and Freundlich (R2 = 0.993) isotherm, preferably Freundlich model. The pseudo-second-order kinetic model (R2 = 0.999) was fitted better, i.e. chemisorption. The equilibrium adsorption capacity was 135.34 ± 1.59 mg/g at 298 K, which was decreased to 125.34 ± 1.81, 114.27 ± 1.43, and 104.08 ± 1.53 mg/g at 308, 318 and 328 K, respectively. Negative Gibbs free energy (ΔG) revealed that adsorption of AR 73 dye on PP was spontaneous. In real sample analysis, about 98.17 ± 0.58 % dye removal was obtained with 137.39 ± 2.46 mg/g capacity. This research revealed that PP has a good prospect for the application of AR 73 dye removal from leather dyeing effluent.